NFC secured online transaction in mobile computing business - Mantoro, Teddy; Ayu, Media Anugerah; Brotosaputro, Gunawan; Ain, Nur F.; Ghazali, Noorzalina (University Press, 2012)
The growth and expansion of the Internet come in a rapid speed and took important place in many aspects of lives, including online payment for transaction information. NFC technology has become a success across a broad range of applications depending on its large-scale adoption by enterprises and consumers. Unfortunately, NFC security is still a major concern for the business. This study proposes a secure mobile transaction model for any transaction using NFC Technology. As proof of concept, a Top-up printing system is developed and for interaction with contactless interface, an ACR 100 Reader with ACOS3 SIM card is used. As for the security measurement, MD5 algorithm is implemented to process the system authorization. As a result of employing NFC Technology, the users no longer need to wait in a long queue. Just “touch” or “wave” at the nearest reader to top-up.